Diagnostic and Prognostic Impact of Crypt Branching in Patients With Ulcerative Colitis: A Validation Study - Lang-Schwarz, Corinna; Rubio, Carlos A.; Vieth, Michael (Anticancer Research, 2022)
Background/Aim: This study aimed to validate the inter-rater agreement of the assessment of crypt branching (also called crypt fission) in patients with ulcerative colitis (UC) and to elucidate its potential diagnostic and prognostic impact. Patients and Methods: A total of 100 biopsies from patients with UC were analyzed. Two cohorts of 50 patients each served as controls [infectious controls/controls with low grade intraepithelial neoplasia (LGIN) in UC alio loco]. Three pathologists scored the number of total crypts in fission as well as the number of crypts in symmetric (CSF) and asymmetric fission (CAF). Results: Inter-rater agreement ranged from good to excellent in the study cohort. The number of crypts in fission correlated significantly with UC-activity (p=0.001; p<0.001). The study cohort showed higher mean counts of crypts in fission and significant more total and CAF than the infectious controls (p=0.007 and p=0.008), especially in male patients (p<0.001) The LGIN-control cohort showed significant more CSF (p=0.012). Conclusion: Inter-rater agreement for crypt branching was reliable in the study cohort. Crypt branching proved as an additional histologic feature to distinguish active UC against infectious colitis. Higher amounts of CSF may help identifying patients at higher risk for neoplasia.
CRIS-Team WoS Importer:2022-01-21